Is the Traditional Chinese Herb "Bombax Malabaricum" a Natural Anticancer Medicine? - Siukan Law; Chuiman Lo; Jie Han; Albert Wingnang Leung; Chuanshan Xu (Korean Pharmacopuncture Institute, 2022)
Cervical spondylotic myelopathy (CSM) is common in elderly people and severe CSM patients are recommended to receive surgery. However, in some cases, surgery may fail to improve the patients' symptoms. An 80-year-old man diagnosed with CSM complained of right hemiplegia and right arm and leg pain with the presence of a Foley catheter, despite treatment with laminectomy and laminoplasty. Acupuncture, bee venom pharmacopuncture, and herbal medicine were administered for 129 days. As a result, manual muscle testing (MMT) and the Modified Barthel Index (MBI) improved, the pain in his right arm and leg decreased, and he was able to urinate by himself. This case report implies that integrative Korean medicine (IKM) can be an option for patients suffering from muscular weakness resulting from myelopathy.